Influencia del uso de lentes de contacto en la microbiota bacteriana ocular humana. (2021)
In the ocular microbiota there are bacteria of the genera Staphylococcus, Corynebacterium spp., Bacillus spp., Neisseria spp., Moraxella spp. And Streptococcus spp (1). However, it has been described that the composition of the communities fluctuates according to factors such as temperature, age, sex, environmental exposure and exposure to foreign bodies (1,2). Aspects such as prolonged use, the lack of asepsis of both the contact lens and the case where they are deposited, and the state of the cleaning fluids have been identified. These aspects lead to the identification of the use of contact lenses as a factor of risk for the development of eye disorders (1,2). Objective: To determine the influence of the use of contact lenses on the human ocular bacterial microbiota. Methodology: bibliographic review, ocular surface, cornea and contact lenses. A search of published articles of the last 10 years was carried out; taking into account the inclusion and exclusion criteria. Results: the bacteria with the highest frequency in the normal ocular microbiota were identified, which were Staphylococcus, Streptococcus, bacillus, and those with the highest frequency in contact lenses were: Staphylococcus aureus, Staphylococcus epidermis, Klepsiella pneumonide and Citrobacter diversus. Conclution: